2019
DOI: 10.1186/s40657-019-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capture and captivity on plasma corticosterone and metabolite levels in breeding Eurasian Tree Sparrows

Abstract: Background: Bringing free-living animals into captivity subjects them to the stress of both capture and captivity, leading to the alteration of normal physiological processes and behaviors through activation of the hypothalamicpituitary-adrenal axis. In free-living birds, although elevated plasma corticosterone (CORT) is an important adaptation regulating physiological and behavioral responses during the process of capture and captivity stress, little information is currently available on the effects of such s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 61 publications
3
23
0
Order By: Relevance
“…Serum corticosterone has also been reported to be an unreliable measure of chronic stress due to hunger [23,38]. Furthermore, corticosterone is highly mobilized when a bird is captured and handled for long, making its measurement and interpretation difficult [39,40]. The H/L ratio may be a more consistent indicator of social stress than plasma corticosteroid levels [41].…”
Section: Table-3mentioning
confidence: 99%
“…Serum corticosterone has also been reported to be an unreliable measure of chronic stress due to hunger [23,38]. Furthermore, corticosterone is highly mobilized when a bird is captured and handled for long, making its measurement and interpretation difficult [39,40]. The H/L ratio may be a more consistent indicator of social stress than plasma corticosteroid levels [41].…”
Section: Table-3mentioning
confidence: 99%
“…In this study, we assumed that all the birds have experienced 2h acute stress of capture and restraint in the cages without food and water deprivation. Although in our previous studies several physiological parameters of the breeding Eurasian tree sparrows exhibited irregular changes in response to acute stress, some of them could return to their normal states within the first hour of capture stress (34,38,39,41). Given that some physiological parameters could have changed during capture, handling, and restraint stress, therefore, further investigations are warranted to consider the effects of stress-induced physiological alternations on both HPT-and HPG-axes during the breeding period.…”
Section: Limitationsmentioning
confidence: 86%
“…Our previous studies showed that testis size and plasma testosterone of male ETSs varied with breeding sub-stages, which are associated with body condition and corticosteroidbinding globulin (CBG; a proxy of energetic condition) (34,35,38). In addition, plasma metabolites including TC, TG, Glu, and uric acid (UA; a product of protein degradation) levels have been investigated and varied with external environmental conditions (39).…”
Section: Introductionmentioning
confidence: 99%
“…As birds have a great number of specific groups, different groups can be used to assess the plastic pollution burden, long-term effects of MPs exposure in various environments, and toxicological effects in the laboratory. For instance, human commensal species, such as the Eurasian Tree Sparrow (Sun et al 2016 ; Li et al 2019 ; Yang et al 2019 ; Ding et al 2021 ), House Sparrow ( P. domesticus ) (Hanson et al 2020 ) and House Wren ( Troglodytes aedon ) (Juárez et al 2020 ) utilize human resources in rural and urban areas and have a remarkably broad distribution range. These species could be used as bioindicators to evaluate the plastic pollution burden in different environments because they have been well studied in the past two decades.…”
Section: Future Directionsmentioning
confidence: 99%